From Secret Code to Mainstream: The Rise of Gay Vernacular in Filipino Society - Garcia, Wyneth Beatriz B.; Montemayor, Vince John A.; Cosme, Princess Angela M.; Sundiam, Francine Danielle L.; Famorcan, Eirene Nicole B.; Galindez, Angelica Ross G.; Carlos, Julius L.; Simon, Christian Louie C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aimed to explore how social media and social platforms influenced the mainstreaming of gay vernacular and its impact on cultural expression and identity. This qualitative research paper utilized a phenomenological approach to know the experiences and perspectives of both the heterosexual and homosexual participants in the municipality in region 3. Through thematic analysis of focus group discussions, the findings revealed that social media platforms have significantly contributed to the normalization and acceptance of gay language. Along with the growing acceptance within the gay community, several issues also arose, such as misinterpretation and cultural appropriation.  The challenges highlighted the need to further study and understand the gay language, as well as the importance of cultural sensitivity in using it. Despite these challenges, the integration of gay vernacular into everyday language enhanced the visibility and acceptance of LGBTQ+ identities. The findings of this study enabled the researchers to create a community language-based framework or the ACCLA Framework. Researchers can use this framework to further strengthen their study. This phenomenon underscored the relationship between language, culture, and identity. This research has served as evidence of the transformative power of language and its ability to promote inclusivity and foster understanding within the community.